Teaching children to think - Fisher, Robert, 1943- (Cheltenham: Nelson Thornes, 2005)
This book describes and analyzes programs and approaches to the teaching of thinking from all around the world, providing ideas for teachers to use in their own classrooms. With new summaries for each chapter, this new updated version includes more practical ideas to start the day thinking. Teaching Children to Think features more on emotional intelligence, cognitive acceleration, and the use of ICT in teaching thinking; while also providing more on assessment, new resources, and web links.
includes bibliographical references and index
Keywords: Critical thinking in children -- Study and teaching (Elementary); Thought and thinking -- Study and teaching (Elementary); Learning, Psychology